2017
DOI: 10.1186/s13643-017-0573-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of community pharmacy public health interventions on population health and health inequalities: a systematic review of reviews protocol

Abstract: BackgroundCommunity pharmacies have great potential to deliver services aimed at promoting health and preventing disease, and are embedded within communities. In the light of a rapid increase in community pharmacy-delivered public health services and an accompanying increase in the evidence base, this systematic review of reviews will synthesise systematic reviews of public health community pharmacy interventions and assess their effects on public health and health inequalities.Methods/designSystematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In this context, two levels of analysis were important: feeling and opinion. At the first level, the survey dealt with a pharmacy, and, hence, a pharmacist: this is viewed with greater recognition and appreciation for expressing humanity under difficult circumstances: terms such as empathy and helpfulness emerged in describing the behaviour of this figure during the pandemic, especially in light of the sense of disorientation exacerbated by the difficulty in gaining access to healthcare professionals and health centres, unlike community pharmacies [ 9 , 10 ]. Turning to the term opinion: on one hand, the research confirmed the perception that the pharmacy was an irreplaceable institution whose presence represented then, and now, as a reference point for members of the public who experienced difficulties in accessing healthcare structures; on the other hand, respondents expressed a desire for greater cooperation between pharmacists and family doctors, which is strictly limited by current legislation in Italy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, two levels of analysis were important: feeling and opinion. At the first level, the survey dealt with a pharmacy, and, hence, a pharmacist: this is viewed with greater recognition and appreciation for expressing humanity under difficult circumstances: terms such as empathy and helpfulness emerged in describing the behaviour of this figure during the pandemic, especially in light of the sense of disorientation exacerbated by the difficulty in gaining access to healthcare professionals and health centres, unlike community pharmacies [ 9 , 10 ]. Turning to the term opinion: on one hand, the research confirmed the perception that the pharmacy was an irreplaceable institution whose presence represented then, and now, as a reference point for members of the public who experienced difficulties in accessing healthcare structures; on the other hand, respondents expressed a desire for greater cooperation between pharmacists and family doctors, which is strictly limited by current legislation in Italy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is where community pharmacies come into their own: not only safeguarding public health but, moreover, taking over the care of patients and participating actively in reducing health disparity [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving forward and based on the positive experiences of participants with lived experience of mental illness and addictions in the Bloom Program, it will be important to evaluate pharmacy practice interventions from a lens of reducing inequalities and inequities. A recently published systematic review protocol by Hillier-Brown et al, 15 regarding community pharmacy public health interventions’ effects on population health and health inequalities, highlights an important step in this direction. In their methods, PROGRESS-Plus criteria are used in which PROGRESS refers to place of residence, race/ethnicity/culture/language, occupation, gender/ sex, religion, education, socioeconomic status and social capital, and “Plus” is in reference to personal characteristics associated with discrimination (e.g., age, disability), features of relationships (e.g., excluded from school) and time-dependent relationships (e.g., leaving the hospital).…”
Section: Discussionmentioning
confidence: 99%
“…In their methods, PROGRESS-Plus criteria are used in which PROGRESS refers to place of residence, race/ ethnicity/culture/language, occupation, gender/ sex, religion, education, socioeconomic status and social capital, and "Plus" is in reference to personal characteristics associated with discrimination (e.g., age, disability), features of relationships (e.g., excluded from school) and time-dependent relationships (e.g., leaving the hospital). 15,16…”
Section: Participantsmentioning
confidence: 99%